The EAPC framework on palliative sedation and clinical practice—a questionnaire-based survey in Germany - Klosa, Philipp; Klein, Carsten; Heckel, Maria; Bronnhuber, Alexandra C.; Ostgathe, Christoph; Stiel, Stephanie (Supportive Care in Cancer, 2014)
Background: Palliative sedation (PS) can be offered to patients with intolerable symptom burden refractory to comprehensive palliative care (PC) treatment. Little is known about the daily practice of using PS in German specialized PC institutions in the context of existing national and international recommendations.
Keywords: Deep sedation; Guideline adherence; Palliative care; Practice guidelines as topic; Symptom control